1982
DOI: 10.1016/0049-0172(82)90030-0
|View full text |Cite
|
Sign up to set email alerts
|

Frozen shoulder

Abstract: The term Frozen Shoulder (FS) is a medical colloquialism rather than a diagnosis. It is usually used as a clinical description with pathogenetic inferences, as suggested by the alternative designations of periarthritis, pericapsulitis, adhesive capsulitis and obliterative bursitis. Our understanding of the basic pathology and natural history of FS is limited, and this is reflected in the wide assortment of treatments which have been advocated. In this review the present state of knowledge of this disorder will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
70
0
1

Year Published

1984
1984
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 124 publications
(72 citation statements)
references
References 36 publications
1
70
0
1
Order By: Relevance
“…103 A greater than 50% reduction in passive external rotation or less than 30° of external rotation, when measured with the arm at the side, is a common finding in individuals with frozen shoulder. 8,15,18,24,39,78,96,100,107,119,121 Although authors of textbooks have described patients with frozen shoulder as having normal strength and painless resisted motions, 24 authors of recent studies, using handheld dynamometry, have revealed significant weakness of the shoulder internal rotators 53,59 and elevators 53,59,111 in these patients. The shoulder internal rotators were significantly weaker in patients with frozen shoulder compared to patients with rotator cuff tendinopathy; however, significant weakness of the external rotators and abductors was also found relative to the uninvolved side.…”
Section: Level 5 J Orthop Sportsmentioning
confidence: 99%
See 2 more Smart Citations
“…103 A greater than 50% reduction in passive external rotation or less than 30° of external rotation, when measured with the arm at the side, is a common finding in individuals with frozen shoulder. 8,15,18,24,39,78,96,100,107,119,121 Although authors of textbooks have described patients with frozen shoulder as having normal strength and painless resisted motions, 24 authors of recent studies, using handheld dynamometry, have revealed significant weakness of the shoulder internal rotators 53,59 and elevators 53,59,111 in these patients. The shoulder internal rotators were significantly weaker in patients with frozen shoulder compared to patients with rotator cuff tendinopathy; however, significant weakness of the external rotators and abductors was also found relative to the uninvolved side.…”
Section: Level 5 J Orthop Sportsmentioning
confidence: 99%
“…100 Although the precise etiology remains unclear, recent evidence identifies elevated serum cytokine levels as part of the process. 19,49,101 Cytokines and other growth factors facilitate tissue repair and remodeling as part of the inflammatory process.…”
Section: Level 5 J Orthop Sportsmentioning
confidence: 99%
See 1 more Smart Citation
“…The frozen shoulder may in fact be a forme fruste of the shoulder-hand syndrome (9). The association of hyperthyroidism with either lends further support to the notion that they are related.…”
Section: Brief Report Frozen Shoulder In Hyperthyroidism Jeffrey R Wmentioning
confidence: 51%
“…Stroke, spinal cord injury, and diabetes are prominent among the conditions that predispose to frozen shoulder (9) and the shoulder-hand syndrome (10). Dysfunction of the autonomic nervous system is thought to be of pathogenic importance.…”
Section: Brief Report Frozen Shoulder In Hyperthyroidism Jeffrey R Wmentioning
confidence: 99%